PENGARUH KONDISI KEUANGAN, RASIO KEGAGALAN HUTANG, UKURAN PERUSAHAAN DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP PENERIMAAN OPINI GOING CONCERN - Ardianto, Yuli (Manajemen Bisnis Kompetensi, 2014)
ABSTRACTÃÂ The use of financial condition variable and the debt default is based on the assumption that Going Concern Opinion (GCO) is given only when the company experience financial distress. The size of the company, then, is used as variable due to the reason that the bigger the company, the easier it is to overcome the financial distress as it has stronger board of management. Therefore, the possibility to accept GCO is less compare to the smaller company. Professional accountant public offices keep their reputation by giving opinion according to the auditing result even when they have financial distress and is being audited by bigger Public Accountant Office. The possibility to receive GCO is bigger. The results showed that the financial condition of all significant variables, all three have a significance level of less than 5%. Financial ratios reflect the companys ability to complete its obligations so that all three ratios may affect the likelihood of receiving going-concern opinion. While the other variables, including the failure of debt, company size and reputation of a public accounting firm, they were not significant because it has a greater significance level of 5%. This indicates that the auditor only concerned with financial factors will make a decision at the time of going concern opinionÃÂ Keywords: Going Concern Opinion, Financial Ratio, Reputation Of Accountant Public, ÃÂ Financial ConditionÃÂ ÃÂ